Supply and demand for cereals in Pakistan, 2010-2030 - Nazli, Hina; Haider, Syed Hamza; Sheik, Asjad Tariq (International Food Policy Research Institute, 2012)
This paper presents the projections of future demand and supply for these two main cereals for 2010, 2015, 2020, 2025, and 2030. For projecting household demand, the Almost Ideal Demand System (LA-AIDS) is estimated for eight food items using the data of nationally representative household survey. The results are used to project the household demand under three different scenarios. These scenarios are: a business-as-usual situation (per capita income is assumed to grow at a rate of 3 percent per year), an optimistic situation (assumed growth rate of per capita income 4 percent per year), and a pessimistic situation (per capita income is assumed to grow by 2 percent per year). Cereal supply is projected using a short-run production function approach (with such variables as area and share irrigated fixed exogenously at observed levels). This projection is then used to estimate the levels of wheat and rice produced for 2009–2030, with the projections of the exogenous determinants of production based on linear time trend models. The results show that the demand for wheat and rice will more than double by 2030. The projections of supply show an increase in the output of wheat and rice by 2030. From 2008 to 2030, the demand for wheat will increase from 19 million tons to 30 million tons. Projection estimates of wheat supply based on the production function technique show that by 2030, wheat output will reach 28 million tons, and rice output will be 11 million tons. The demand for wheat is expected to be greater than its supply whereas production of rice will be higher than consumption.